Segregation texts: Riksdag's open data: Swedish Government Official Reports (SOU series) - Språkbanken Text (University of Gothenburg, 2024)
Olika utredningars förslag till regeringen
Segregationstexter: Riksdagens öppna data: Statens offentliga utredningar
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik